Target Costing Implementation Product Design and Product Process Conducted By Yamaha- Motor Kencana Indonesia (YMKI) - Yahya, Johannes (Jurnal Manajemen (Edisi Elektronik), 2018)
The purpose of this study are to know target costing implementation in Yamaha- MotorKencanaIndonesia(YMKI),andevaluatethewayofcompanytomakeproductdesign and process in reaching the target costing after determining price and profit. The firm was success in implementing target costing, this can be seen by good Product functionality and market share achievement. Product design and product process conducted by Yamaha-Motor Kencana Indonesia (YMKI) was able to sustain product quality, and not only could make stability in market share but olso have got wider market share. The way of company to make product design and process in reaching the target costing after determining price and profit is applying value engineering technique that is a cost reduction and process improvement technique that utulizes information collected about a product, design and process to indentify candidates for improvement efforts.